Índice de severidade e SIG combinados para identificar e caracterizar a sinistralidade de trânsito em município de pequeno porte - Bellintane Júnior, Cláudio (Universidade Federal de São Carlos, 2025)
The disorderly growth of cities has caused many urban problems, including unplanned urban mobility focused on motor vehicles, resulting in numerous traffic accidents, loss of life, and significant social and economic losses. This growth has also affected small cities, such as the city of Novo Horizonte/SP, the object of this research. The city has approximately 39 thousand inhabitants and a fleet of more than 32 thousand vehicles. In addition, the urban mobility problems are the same as in large cities, although to a lesser extent, but causing similar effects. Given the above, this research combines the severity index, through the calculation of the UPS, with GIS to identify the critical points of accidents in the city of Novo Horizonte. The methodology applied consisted of collecting accident data from the period between 2018 and 2023 from police reports prepared by the Military Police of the State of São Paulo. Based on the processing and systematization of the data, the severity index was calculated to define the critical points, according to the severity of each traffic accident. The data was then georeferenced in a GIS, from which it was possible to create Kernel Density Maps that showed the areas with the highest concentration of severity. The research identified the roads and critical points with the highest severity, in addition to analyzing the times and days of the week related to the accidents. Detailed data on victims revealed that the most vulnerable groups (motorcyclists, pedestrians, and cyclists) require priority in actions and interventions since they represented 70.83% of the total deaths recorded in the period from 2018 to 2023.
Severity index and GIS combined to identify and characterize traffic accidents in a small municipality
Keywords: Segurança viária; Sinistros de trânsito; Sistema de Informação Geográfica; Mapa de densidade de Kernel; Índice de severidade; Road safety; Traffic accidents; Geographic Information System; Kernel density map; Severity index; ENGENHARIAS::ENGENHARIA DE TRANSPORTES; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES